2019
DOI: 10.1111/imb.12590
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the neural sex‐determination system in insects: does fruitless homologue regulate neural sexual dimorphism in basal insects?

Abstract: In the brain of holometabolous insects such as the fruit fly Drosophila melanogaster, the fruitless gene produces sex‐specific gene products under the control of the sex‐specific splicing cascade and contributes to the formation of the sexually dimorphic circuits. Similar sex‐specific gene products of fruitless homologues have been identified in other holometabolous insects such as mosquitoes and a parasitic wasp, suggesting the fruitless‐dependent neural sex‐determination system is widely conserved amongst ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…The putative sequences of Pmfru-1 and Pmfru-2 exhibited highly conserved BTB domain and ZF domains. Fruitless have been identified in several insect and crustacean species, including many species in Drosophilidae, Nasonia vitripennis , Gryllus bimaculatus , and Chinese mitten crab E. sinensis ( Bertossa, Van de Zande & Beukeboom, 2009 ; Li et al, 2017 ; Ryner et al, 1996 ; Watanabe, 2019 ; Zollman et al, 1994 ). We showed that Pmfru-1 and Pmfru-2 could be derived from the same genomic locus by mutually-exclusive-exons alternative splicing of the Pmfru pre-mRNA ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The putative sequences of Pmfru-1 and Pmfru-2 exhibited highly conserved BTB domain and ZF domains. Fruitless have been identified in several insect and crustacean species, including many species in Drosophilidae, Nasonia vitripennis , Gryllus bimaculatus , and Chinese mitten crab E. sinensis ( Bertossa, Van de Zande & Beukeboom, 2009 ; Li et al, 2017 ; Ryner et al, 1996 ; Watanabe, 2019 ; Zollman et al, 1994 ). We showed that Pmfru-1 and Pmfru-2 could be derived from the same genomic locus by mutually-exclusive-exons alternative splicing of the Pmfru pre-mRNA ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Fru in controlling brain organization for male sexual behaviour in other insects is largely unknown. Despite this, recent research suggests that in basal hemimetabolous insects, Fru is not sex‐specifically spliced and is not likely to be involved in neural sex determination (Watanabe, 2019). However, even in Drosophila , all neuronal clusters expressing Dsx are either sex‐specific or sexually dimorphic and none are sexually monomorphic (Nojima et al, 2021).…”
Section: Sex‐determination and The Birth Of Neuronsmentioning
confidence: 99%
“…Other studies have suggested that gynandromorphs' sexual behaviours may be more strongly influenced by the head (brain) rather than by the abdomen (reproductive organs) (Yoshizawa et al 2009). Under effect of sex-specific fruitless (fru) gene products, neurones of the insect brain form sexually dimorphic circuits, regulating sexual behaviours such as courtship and aggression (Watanabe 2019). Matsuo et al (2018) have analyzed the encephalic and antennal expression patterns of the fru gene in a Bombus ignitus gynandromorph with a bilaterally dimorphic head and thorax (left side-male, right side-female) and a uniformly masculine gaster.…”
Section: Behaviourmentioning
confidence: 99%